2014
DOI: 10.1111/jvim.12339
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Beta Blockers on Survival in Dogs with Severe Subaortic Stenosis

Abstract: BackgroundSubaortic stenosis (SAS) is one of the most common congenital cardiac defects in dogs. Severe SAS frequently is treated with a beta adrenergic receptor blocker (beta blocker), but this approach largely is empirical.ObjectiveTo determine the influence of beta blocker treatment on survival time in dogs with severe SAS.MethodsRetrospective review of medical records of dogs diagnosed with severe, uncomplicated SAS (pressure gradient [PG] ≥80 mmHg) between 1999 and 2011.ResultsFifty dogs met the inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Administration of beta-blockers can decrease heart rate, prolong diastole and coronary filling, thereby reducing myocardial hypoxia and protect against arrhythmia. Dogs do clinically well on beta-blockers; however, a study proved no benefit in terms of survival versus untreated dogs with severe SAS [59]. There is no literature on evaluation of other medical treatment.…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…Administration of beta-blockers can decrease heart rate, prolong diastole and coronary filling, thereby reducing myocardial hypoxia and protect against arrhythmia. Dogs do clinically well on beta-blockers; however, a study proved no benefit in terms of survival versus untreated dogs with severe SAS [59]. There is no literature on evaluation of other medical treatment.…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…The severity of stenosis ranges from “equivocal” to “severe” (Hollmer et al , Stern et al , ), and outcomes for dogs with pulmonic or subaortic stenosis are dependent on the severity. In most cases, mild stenosis is well tolerated and infrequently affects survival, whereas severe stenosis can result in sudden death or, rarely, congestive heart failure and often warrants medical, surgical or endovascular intervention (Kienle et al , Johnson et al , Eason et al ). Both forms of stenosis present with murmurs, and screening exams usually rely on the accurate characterisation of the murmurs, both in intensity and location.…”
Section: Introductionmentioning
confidence: 99%
“…) of aortic stenosis in dogs have failed to show a survival benefit over medical therapy (beta‐blockers), while a recent study of dogs with aortic stenosis showed no survival benefit for therapy with beta‐blockers over no therapy (Eason et al . ). Furthermore, some interventional procedures are associated with perioperative risk, including cardiopulmonary arrest (Margiocco et al .…”
mentioning
confidence: 97%